Molecular and phylogenetic analysis of herpesviruses in endangered free-ranging cervids of Chile: ovine gammaherpesvirus-2—A novel threat to wild and domestic animal health in Chilean Patagonia - Hidalgo-Hermoso, Ezequiel; Cabello, Javier; Lopez, Rodrigo; Vergara-Wilson, Vicente; Vera, Frank; Valencia, Carola; Sanchez, Carlos; Celis, Sebastian; Silva, Alejandra; Cariñanos, Aintzane; Barria, Ismael; Vicencio, Rocio; et al. (Frontiers in Veterinary Science, 2024)
Herpesvirus infections have been associated withhighlighted as emerging diseases affecting wildlife health and the conservation of several taxa., including species of ruminants with Malignant Catarrhal Fever (MCF) and infectious keratoconjunctivitis (IKC) are two these viruses that infect wild ruminants. Nevertheless, epidemiological data on herpesviruses in South American wild ruminants isare limited. An outbreak of caprine gammaherpesvirus-2 (CpHV-2) that, recently was suspected as the of cause ofing MCF in southern pudus (Pudu puda), generated prompted the needcessity to conduct molecular screenings in Chilean cervids to understand the epidemiology of this and other herpesviruses. The aim of this study was to determine the occurrence and genetic diversity of herpesviruses in free-ranging cervids from Chile. Herpesvirus infection was assessed in antemortem blood samples (n=86) from pudu (n=81) and huemul (Hippocamelus bisulcus) (n=5), and postmortem samples of spleen (n=24) and lung (n=3) from pudus using a nested pan-herpesvirus-PCR assay. Combining all suitable sample types, DNA of pudu gammaherpesvirus-1 was detected in five pudus and five huemuls, with an overall prevalence of 9.90% (n = 10/101; 95% CI = 5.11 -17.87%), one pudu positive to ovine gammaherpesvirus-2 (n = 1/96; 1.04%; 95% CI = 0.05 -6.49%), and one pudu positive to a Macavirus sequence 98.63 identical to ovine gammaherpesvirus-2 (n = 96; 1.04%; 95% CI = 0.05 -6.49%). To the best of our knowledge, this is the first report of a herpesvirus in huemul and of ovine gammaherpesvirus-2 in Chile. Our results also confirm the active circulation of herpesvirus in free-ranging cervids in Chilean Patagonia and as such MCF should be considered as a possible cause of disease in free-ranging Chilean pudu and livestock species. Further research is necessary to develop a plan of systematic monitoring (serological and pathological screening) of herpesviruses in Chilean wild and domestic ruminants to understand their diversity and impact on animal health and conservation.